2011
DOI: 10.1590/s1678-77572011000500007
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of Calendula officinalis, Camellia sinensis and chlorhexidine against the adherence of microorganisms to sutures after extraction of unerupted third molars

Abstract: ObjectiveThe objective of this study was to compare the antimicrobial effect of mouthwashes containing Calendula officinalis L., Camellia sinensis (L.) Kuntze and 0.12% chlorhexidine digluconate on the adherence of microorganisms to suture materials after extraction of unerupted third molars. Material and MethodsEighteen patients with unerupted maxillary third molars indicated for extraction were selected (n=6 per mouthwash). First, the patients were subjected to extraction of the left tooth and instructed not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 28 publications
1
23
0
5
Order By: Relevance
“…The effects of the use of chlorhexidine and warm saline mouth washes on bacterial growth on chromic catgut and vicryl are not appreciable (P [ 0.05).The effects of mouthwashes on healing process shows that chlorhexidine, in a concentration and time-dependent manner, affects negatively, fibroblasts and keratinocyte cell proliferation in vitro and can impair wound healing [8].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The effects of the use of chlorhexidine and warm saline mouth washes on bacterial growth on chromic catgut and vicryl are not appreciable (P [ 0.05).The effects of mouthwashes on healing process shows that chlorhexidine, in a concentration and time-dependent manner, affects negatively, fibroblasts and keratinocyte cell proliferation in vitro and can impair wound healing [8].…”
Section: Discussionmentioning
confidence: 98%
“…This situation is favored or prevented, depending on the adsorption properties of the suture material and oral hygiene care of the patient during the postoperative period [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported satisfactory results with the antimicrobial effect of GT on C. albicans and other microorganisms . In the current study, both conventionally and microwave‐polymerised acrylic resins were used to simulate the formation of biofilm of C. albicans on the prosthesis into the oral cavity.…”
Section: Discussionmentioning
confidence: 96%